STATUS DEBRIS INDEX SEBELUM DAN SESUDAH DILAKUKAN DEMONSTRASI MENYIKAT GIGI DENGAN CARA ROLL TECHNIC PADA SISWA KELAS IV & V SEKOLAH DASAR KARTIKA XXI-5 MANADO - Ni Made Yuliana; Jeineke E. Ratuela; Jeana L. Maramis; Yenny Lisbeth Siahaan (Poltekkes Kemenkes Medan, 2024)
Demonstration of how to brush teeth is a teaching method by presenting lessons through direct demonstration of the object or showing a process or procedure. Roll Technique is the method most often recommended because it is simple but efficient and can be used throughout the mouth. Debris Index (DI) is a score (value) of soft deposits that occur due to food residue attached to the tooth surface. This study aims to determine the status of the debris index before and after a demonstration of brushing teeth using the roll technique. The type of research is experimental research with a One Group Pretest-Posttest design. The total population was 52 students and the total sample was 48 students, the time of the research was in May 2019 at Kartika XXI-5 Manado Elementary School. This research was to see the difference in debris index status before and after the demonstration method of brushing teeth using the roll technique using a paired sample t test. The results of this study showed that the average debris index before the demonstration of brushing teeth using the roll technique for 48 respondents was 2.31, while the average debris index after the demonstration of brushing teeth using the roll technique for 48 respondents was 1.48. The calculated t value is 10.335 with a sig of 0.000. because sig <0.05, it can be concluded that Ho is rejected and H1 is accepted, which means there is a difference in the status of the debris index before and after a demonstration of brushing teeth using the roll technique for students in class IV & V at Kartika XXI-5 Elementary School, Manado.